Multilingual Thesaurus of Industry-Specific Terms as Major Aids for Translators - Bayekeyeva, Ainur T.; Tazhibayeva, Saule Zh.; Shaheen, Aigul A.; Beisenova, Zhainagul S.; Mamayeva, Gulnar B. (Opción)
This paper discusses the theoretical and methodological issues of compiling multilingual thesaurus for conducting industry-specific translation in the mining industry as one of the key genres of translation studies that bear difficulties in translating the technical documents. In market realism of Kazakhstan, industry-specific translations are one of the most popular types of translation services. It is reasonably considered that only a translator with technical background with the knowledge of the subject field is able to translate a technical text well, i.e. an industry-specific technical translator who understands the essence of the matter, the so-called ‘engineering competent translation